Effective generation of functional pancreatic β-cells from human derived dental stem cells of apical papilla and bone marrow derived stem cells - Duaa Abuarqoub (6672434) (2023)
Poster by Duaa Abuarqoub (University of Petra), Sofia Adwan (American University of Madaba), Rand Zaza (University of Jordan), Suha Wehaibi (University of Jordan), Nazneen Aslam (University of Jordan), Hanan Jafar (University of Jordan), Nidal Qinnah (University of Petra), and Abdalla Awidi (University of Jordan)  Background: Diabetes Miletus Type 1  is an autoimmune disease that occurs due to the destruction of insulin producing cells (β cells), resulting in hyperglycemia. Therefore, diabetic patients depend on the insulin treatment for the rest of their lives. Stem cells are considered a promising cellular therapy to replace the nonfunctional beta cells with functional and mature beta cells. Objective: Hence, in this study we aimed to examine the potential of dental stem cells of apical papilla (SCAP) to differentiate into functional islet like cell aggregates (ICAs), compared to the ICA generated from Bone marrow derived stem cells (BM-MSCs). Methods: Our strategy was to induce the differentiation of SCAP and BM-MSCs into definitive endoderm. The success of endodermal differentiation was determined by measuring the expression of definitive endodermal markers; FOXA2 and SOX-17 by flow cytometry. Next, the maturity and functionality of the differentiated cells was evaluated by measuring the amount of insulin and C-peptide secreted by the derived ICAs using ELISA. Additionally, the expression of mature beta cell markers; Insulin, C-peptide, Glucagon and PDX-1 was detected through confocal microscopy, while the staining of the mature islets like clusters by using diphenythiocarbazone (DTZ). Results: Our results have shown that both SCAP and BM-MSCs were sequentially committed to definitive pancreatic endoderm, and β-cell like cells by upregulating the expression of FOXA2 and SOX17 significantly (p****<0.0000 and p***=0.0001) respectively. Moreover, the identity of ICAs was confirmed by DTZ-positive staining, as well as by the expression of C-peptide, Pdx-1, insulin, and glucagon at day14. It was noted that at day14, differentiated-ICAs released insulin and C-peptide in a significant manner (p*<0.01, p***=0.0001) respectively, exhibiting in vitro functionality. Conclusion: Our results demonstrated for the first time that SCAP could be differentiated into pancreatic cell lineage in a similar manner to BM-MSCs, suggesting a new unambiguous and nonconventional source of stem cells that could be used for stem cell therapy to treat diabetes.